AMBIGUITAS PERAN SEBAGAI PREDIKTOR STRES KERJA PADA ANGGOTA BRIMOB BATALYON B PELOPOR POLDA X - Siska Amalia; Yulia Fitriani; Fathana Gina (STKIP Subang, 2026)
This study was motivated by the high work demands experienced by Brimob officers, which may contribute to job stress due to role ambiguity in carrying out their duties. The study aimed to examine whether role ambiguity serves as a predictor of job stress among members of Brimob Battalion B Pelopor Polda X. A quantitative approach with simple linear regression analysis was employed in this research. The sample consisted of 119 male Brimob officers with 1–5 years of service, selected using a quota sampling technique. Data were collected using the Role Ambiguity Scale and the Police Stress Questionnaire (PSQ). The findings revealed that role ambiguity significantly predicted job stress (p < 0.001). Furthermore, the correlation coefficient (R = 0.723) indicated a strong relationship, while the coefficient of determination (R² = 0.523) showed that role ambiguity accounted for 52.3% of the variance in job stress.